ChemInform Abstract: Eco‐Friendly Chemoselective N‐Functionalization of Isatins Mediated by Supported KF in 2‐MeTHF. Issue 51 (December 2015) - Mamuye, Ashenafi Damtew; Monticelli, Serena; Castoldi, Laura; Holzer, Wolfgang; Pace, Vittorio
Abstract: The title method is applicable to a wide range of alkyl halides and acyl donors as well as Michael acceptors.